Influence of Education of Entrepreneurship, Self Efficacy, Locus of Control and Entrepreneurs Characters of Enterprises (The Study Case Is All the Students of Private University in Medan) - Satria Tirtayasa; Hazmanan Khair; Mohammad Yusri (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
Many young people become unemployed, so that fostering an entrepreneurial spirit is believed to be an alternative to overcome limited employment and reducing the number of unemployed. The purpose of this study was to analyze the effect of entrepreneurship education, self efficacy, locus of control and entrepreneurial character in the interest of entrepreneurship among undergraduate students. The location of this research is Muhammadiyah University, North Sumatra Faculty of Business Management, Medan Area University Faculty of Economics and Business, and Islamic University of North Sumatra Faculty of Economics and Business. The three universities were chosen because they already have a business incubator center, the number of samples used was 125 people (Quata sampling). Where research respondents are students who have taken the Entrepreneurship course (purposive sampling). Data collection by questionnaire. Data analysis techniques used, multiple linear regression, simple regression, and determinant coefficients. Based on the partial test (t test), it was found that there was a positive but not significant effect on entrepreneurship education on entrepreneurial interest. This is indicated by t count of 0.512 and sig of 0.610 where sig 0.05, There is a positive and significant effect of self efficacy on entrepreneurial interest. This is indicated by t count of 7.167 and sig of 0.000 where sig 0.05, there is a positive but not significant effect of Locus of Control on entrepreneurial interest. This is indicated by t count of 1.607 and sig of 0.111 where sig 0.05, there is a positive and significant effect of entrepreneurial character on entrepreneurial interest. This is indicated by t count of 4,794 sig of 0,000 where sig 0,05. Based on the results of simultaneous testing there are positive and significant effects of entrepreneurship education, self-efficacy, locus of control and entrepreneurial character on entrepreneurial interest. In the F test results obtained the calculated F value of 81.531 and sig of 0.000, where sig F 0.05. The coefficient of determination (R2) is 0.731.